Method for evaluating durability of fuel cell sealing element

The oxygen atom content on the surface of the fuel cell seal is measured by atomic spectroscopy, and the mathematical model is fitted with the least squares method to evaluate the durability of the seal, solving the problem of difficulty in evaluating the durability of the seal in use in the prior art, and achieving rapid and effective durability evaluation.

CN119830533APending Publication Date: 2025-04-15SUNRISE POWER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411831804.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate the durability of fuel cell seals in use, and traditional methods require special aging equipment and long test cycles.

Method used

The oxygen atom content on the rubber surface was measured by atomic spectroscopy, and the mathematical model of the compression permanent deformation and oxygen atom content was fitted by the least squares method, and the failure of the seal was evaluated based on the critical value of the oxygen atom content of the material.

Benefits of technology

This method can quickly and effectively evaluate the durability of fuel cell seals, reduce test time and equipment requirements, and improve the credibility of the evaluation results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119830533A_ABST
    Figure CN119830533A_ABST
Patent Text Reader

Abstract

The invention discloses a durability evaluation method for a fuel cell sealing element. The method comprises the following steps: acquiring surface oxygen atom content information and a compression permanent deformation retention coefficient of a test sample by adopting an atomic spectrum method; performing polynomial fitting on the data of the corresponding relationship between the compression set retention coefficient and the oxygen atom content by using a least square method to obtain a mathematical model of the relationship between the oxygen atom content on the surface of the sealing element and the compression set retention coefficient; calculating an oxygen atom content critical value of the test sample based on the mathematical model; evaluating whether the sealing element is invalid based on the surface oxygen content information of the sealing element; the method thus enables evaluation of fuel cell seal durability in use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fuel cell life assessment, and in particular to a fuel cell sealing durability assessment method. Background Art

[0002] In the prior art, the University of Electronic Science and Technology of China (authorization number: CN107702905 B) invented a method for predicting the reliable life of a rubber ring based on Weibull distribution. Figure 1 ), which includes the following steps: S1, determine the average growth rate λi of the compression permanent deformation rate εik of the rubber ring sample through a bottom test, and then determine the test time t of the rubber ring sample degradation test plan; S2, according to the rubber ring sample degradation test, obtain the axial initial thickness H0 of the rubber ring sample, the axial thickness Hijk of the rubber ring sample at each detection time point and the compression permanent deformation rate εijk in each test process; S3, according to the compression permanent deformation rate εijk in each test process, use the rubber aging formula and the acceleration model based on the Weibull distribution to predict the life of the rubber ring and analyze the reliability of the rubber ring. Compared with the traditional rubber life prediction method, the present invention obtains a single life prediction value, and obtains a reliable life using the life distribution function, so that the evaluation result has higher credibility. This method is a durability test method based on the mechanical index of compression permanent deformation, which requires special aging equipment and a long test cycle.

[0003] Patent No. (CN115855678 A) provides a method for predicting the life span of fuel cell sealing materials, see Figure 2 . It includes: predicting the lower limit of the life of the rubber sample of the fuel cell sealing material under 80°C, using a hot oven to test the compression permanent deformation performance of the sealing sample, and using the kinetic equation to calculate the life of the sealing material under normal working conditions of the fuel cell; predicting the upper limit of the life of the rubber sample of the fuel cell sealing material under 80°C, placing the sealing sample in a fixture, and using the stress relaxation parameters of the relaxation test equipment sample, and using the kinetic curve formula to quickly calculate the life of the sealing material under normal working conditions of the fuel cell; the test device used includes an upper end cover, an upper sealing cover, a lower sealing cover and a lower end cover arranged in sequence. The technical solution of the present invention can determine the range of the life of the fuel cell sealing material, and also provide an important reference for the design of the fuel cell sealing structure. This method is a durability evaluation method based on mechanical indicators, which requires special stress relaxation aging equipment and a long test cycle.

[0004] For rubber materials, mechanical indicators are generally used as durability evaluation indicators. Usually, special aging equipment is used to perform accelerated life tests. Common life prediction methods include the Arrhenius method, the Dakin method, the curve superposition method, and the kinetic curve method. These methods can only test the aging performance of standard samples, and cannot evaluate the aging degree of sealing samples in use. A method that can evaluate the durability of fuel cell seals in use is needed. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention discloses a fuel cell seal durability evaluation method, which specifically includes the following steps:

[0006] Atomic spectroscopy is used to obtain the oxygen atom content information and compression permanent deformation retention coefficient of the test sample surface;

[0007] The least square method was used to perform polynomial fitting on the data of the corresponding relationship between the compression set retention coefficient and the oxygen atomic content, and a mathematical model of the relationship between the oxygen atomic content on the surface of the test sample and the compression set retention coefficient was obtained.

[0008] Calculate the critical value of oxygen atomic content of the test sample based on the mathematical model;

[0009] Evaluate whether the seal has failed based on the surface oxygen content information of the seal.

[0010] The oxygen atom content is the ratio of oxygen atoms to the sum of the main element contents; the test sample and the aging solution are placed in a compression permanent deformation fixture, wherein the aging solution is a solution mixed with sulfuric acid PH2 and hydrofluoric acid ppm5 in a certain proportion.

[0011] The compression set retention coefficient c is calculated as follows:

[0012]

[0013] In the formula, h0 is the initial height of the sample; h1 is the height of the sample after recovery; h s is the limiter height.

[0014] The mathematical model of the relationship between the oxygen atom content on the surface of the test sample and the compression permanent deformation retention coefficient is obtained in the following way:

[0015] Let P n (t) is a fitting polynomial of degree not exceeding m, m is the number of sample data points, n≤m, of the form Find the polynomial parameter a i , so that Get the minimum value.

[0016] Assume that the critical value K of the oxygen atom content on the surface of the test sample is K. When the oxygen atom content on the surface of the seal is greater than K, the seal fails.

[0017] Since the life of fuel cell seals is usually tested by accelerated life test based on mechanical indicators using dedicated aging equipment, the test time is relatively long. The present invention discloses a fuel cell seal durability evaluation method, which uses atomic spectroscopy to test the oxygen atom content on the rubber surface, uses the least squares method to fit the mathematical model of compression permanent deformation and oxygen atom content, and evaluates whether the seal fails during use based on the extreme value of the material's limiting oxygen atom content. Therefore, this method can evaluate the durability of fuel cell seals during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 is a flow chart of the method in the background technology;

[0020] Figure 2 It is a structural schematic diagram in the background technology;

[0021] Figure 3 A flowchart of a fuel cell seal durability evaluation method disclosed in the present invention;

[0022] Figure 4 It is a schematic diagram of the compression permanent deformation fixture in the present invention;

[0023] Figure 5 It is a schematic diagram of the polynomial fitting curve in the present invention. DETAILED DESCRIPTION

[0024] In order to make the technical solutions and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention are clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention:

[0025] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0026] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0027] like Figure 3 A fuel cell seal durability evaluation method is shown, which specifically includes the following steps: S1: using atomic spectroscopy to obtain the oxygen atom content on the surface of the test sample and the permanent compression deformation of the test sample; S2: performing polynomial fitting on the relationship between the oxygen atom content on the surface of the test sample and the permanent compression deformation; S3: determining the critical value of the oxygen atom content of the material; S4: evaluating whether the test sample has failed based on the surface oxygen content of the test sample.

[0028] Furthermore, atomic spectroscopy was used to test the oxygen atom content on the surface of the sample, that is, XPS equipment was used to detect the oxygen atom content and oxygen atom ratio on the surface of the sample immersed in an oxidizing solution.

[0029] Furthermore, the permanent compression deformation of the test sample is measured, and the permanent compression deformation of the test sample with different immersion times is measured using a fixture.

[0030] Furthermore, a polynomial fitting is performed on the relationship between the oxygen atom content on the surface of the test sample and the compression permanent deformation. That is, the least squares method is used to perform polynomial fitting on the data corresponding to the compression permanent deformation and the oxygen atom content, and a mathematical model of the relationship between the oxygen atom content on the surface of the test sample and the compression permanent deformation is obtained.

[0031] Furthermore, the critical value of the oxygen atomic content of the material is determined, the compression permanent deformation retention coefficient of the test sample is 0.5 as the threshold, and the critical value of the oxygen atomic content of the material is calculated using a mathematical model.

[0032] Furthermore, the failure of the test sample is evaluated based on the surface oxygen content of the test sample, that is, the oxygen atom content on the surface of the test sample is compared with the critical value of the oxygen atom content of the material to determine whether the test sample has failed.

[0033] Example:

[0034] The first step is to use atomic spectroscopy to test the oxygen content of samples immersed in aging solution for different times. The oxygen content refers to the ratio of oxygen atoms to the sum of the main elements. For example, the main elements of silicone rubber include oxygen, silicon and carbon, and the oxygen content is equal to the ratio of the total amount of oxygen atoms to the total content of the three elements.

[0035] Prepare the aging solution by mixing sulfuric acid (PH2) and hydrofluoric acid (ppm5) in a certain proportion. Use the fixture to detect the compression permanent deformation of the test samples at different immersion times. Place the sample and the aging solution in the compression permanent deformation fixture, see attached. Figure 4 The compression permanent deformation fixture is mainly composed of a gland, a base, an O-ring, a nut and a screw, which can realize the compression permanent deformation retention coefficient test of the rubber sample. At least 4 sets of compression permanent deformation fixtures are placed in the oven. The oven temperature can be set to 120℃ or 150℃, and the oxygen atomic content of the samples with different immersion times is tested successively.

[0036] The compression set retention coefficient c is calculated as follows:

[0037]

[0038] In the formula, h0 is the initial height of the sample; h1 is the height of the sample after recovery; h s is the limiter height.

[0039] The second step is to use the least squares method to perform polynomial fitting on the data corresponding to the compression set retention coefficient and the oxygen atom content, and obtain a mathematical model of the relationship between the oxygen atom content on the surface of the test sample and the compression set retention coefficient. n (t) is a fitting polynomial of degree not exceeding m (n≤m), m is the number of sample data points, and is in the form Find the polynomial parameters ai so that Get the minimum value.

[0040] The third step is to determine the critical value of the oxygen atom content of the material. According to the national standard test of "Estimation of service life and maximum operating temperature of vulcanized rubber or thermoplastic rubber using Arrhenius diagram (GB T 20028-2005)", the compression permanent deformation retention coefficient of the test sample is 0.5 as the threshold, and the critical value of the oxygen atom content is calculated using a mathematical model.

[0041] Once the test is completed, the critical value of the oxygen atomic content of the sealing material can be used as a constant value.

[0042] The fourth step is to evaluate whether the test sample has failed based on the surface oxygen content of the test sample. First, the oxygen atom content on the surface of any fuel cell seal is tested, and whether the seal has failed is determined based on the critical value of the oxygen atom content of the material.

[0043] Application Examples

[0044] A fuel cell seal service life assessment method is mainly divided into four steps:

[0045] The first step is to use XPS (atomic spectroscopy) equipment to test the surface oxygen atom content of samples with different aging times. Prepare the aging solution and mix sulfuric acid (PH2) and hydrofluoric acid (ppm5) in a certain proportion. Put the standard sample block and the aging solution into the compression permanent deformation device and clamp it. Put at least 4 sets of compression permanent deformation devices into the oven. The oven temperature can be set to 120°C or 150°C. Test the oxygen atom content of samples with different immersion times. The aging time of the samples is 7 days, 14 days, 21 days, and 28 days respectively. The test data is recorded in the following form: Use atomic spectroscopy to test the oxygen atom content of samples with different immersion times in the aging solution.

[0046]

[0047] The second step is to use the least squares method to fit the test data with a cubic polynomial to obtain the relationship curve between oxygen atom content and compression permanent deformation retention coefficient: y = 5.81-37.93*x^1+94.33*x^2

[0048] -78.75*x^3, fitting error: 99.70%, fitting curve see Figure 5 .

[0049] The third step is to determine the critical value of the oxygen atom content of the material. According to the national standard test of "Estimation of service life and maximum operating temperature of vulcanized rubber or thermoplastic rubber using Arrhenius diagram (GB T 20028-2005)", the compression permanent deformation retention coefficient of the test sample is 0.5 as the threshold, and the critical value of the oxygen atom content of the material is calculated to be 0.53.

[0050] The fourth step is to evaluate whether the test sample has failed based on the surface oxygen content of the test sample. First, test the oxygen atom content on the surface of the fuel cell seal in use, and judge whether the seal has failed based on the critical value of the material's oxygen atom content. If the oxygen atom content on the seal surface is greater than 0.48, the fuel cell seal is considered to have failed.

[0051] The present invention uses atomic spectroscopy to test the oxygen atom content on the rubber surface, uses the least squares method to fit the mathematical model of compression permanent deformation and oxygen atom content, and evaluates whether the seal is invalid according to the critical value of the oxygen atom content of the material. This method can evaluate the durability of fuel cell seals in use.

[0052] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A fuel cell seal durability evaluation method, characterized in that include: Atomic spectroscopy is used to obtain the oxygen atom content information and compression permanent deformation retention coefficient of the test sample surface; The least square method was used to perform polynomial fitting on the data of the corresponding relationship between the compression set retention coefficient and the oxygen atomic content, and a mathematical model of the relationship between the oxygen atomic content on the surface of the test sample and the compression set retention coefficient was obtained. Calculate the critical value of oxygen atomic content of the test sample based on the mathematical model; Evaluate whether the seal has failed based on the surface oxygen content information of the seal.

2. A fuel cell seal durability evaluation method according to claim 1, characterized in that: The oxygen atom content is the ratio of oxygen atoms to the sum of the main element contents; the test sample and the aging solution are placed in a compression permanent deformation fixture, wherein the aging solution is a solution mixed with sulfuric acid PH2 and hydrofluoric acid ppm5 in a certain proportion.

3. A fuel cell seal durability evaluation method according to claim 1, characterized in that: The compression set retention coefficient c is calculated as follows: In the formula, h0 is the initial height of the sample; h1 is the height of the sample after recovery; h s is the limiter height.

4. A fuel cell seal durability evaluation method according to claim 1, characterized in that: The mathematical model of the relationship between the oxygen atom content on the surface of the test sample and the compression permanent deformation retention coefficient is obtained in the following way: Let P n (t) is a fitting polynomial of degree not exceeding m, m is the number of sample data points, n≤m, of the form Find the polynomial parameter a i , so that Get the minimum value.

5. A fuel cell seal durability evaluation method according to claim 1, characterized in that: Assume that the critical value K of the oxygen atom content on the surface of the test sample is K. When the oxygen atom content on the surface of the seal is greater than K, the seal fails.

Citation Information

Patent Citations

  • A reliable life prediction method for rubber rings based on Weibull distribution

    CN107702905B

  • Method for predicting life interval of fuel cell sealing material

    CN115855678A